137Cs DISTRIBUTION PECULIARITIES IN FOREST BIO-GEOCENOSIS COMPONENTS OF UKRAINIAN POLISSIA FRESH WOODS - Melnyk, V. V. (Scientific Progress & Innovations, 2020)
The paper is concerned with 137Cs distribution peculiarities in the forest bio-geocenosis components of the Ukrainian Polissia fresh groves. Investigations were carried out on experimental areas laid in Naro-dyshy Forestry. Before measuring 137Cs specific activity, all samples were dried to air-dry state and homog-enized. The density of soil radioactive contamination was 267±9.6 kBq/m2. 137Cs specific activity in the bio-geocenosis components differed by several orders of magnitude, with the minimum in deep horizontal soil layers (28–30 cm layer – 40 Bq/kg) and the maximum in the above-ground phyto-mass of some plant species (Dryopteris carthusiana (Vill.) – 85,937 Bq/kg). In addition, significant fluctuations in radionuclides specific activity between separate components of forest bio-geocenosis have been identified. Thus, the components of pine stands can be arranged in a line by reducing 137Cs specific activity: shoots > internal bark > needles > outer bark > thin branches > thick branches > tree, while grass-shrub cover is characterized by the follow-ing line: Dryopteris carthusiana (Vill.) > Vaccinium myrtillus L. > Calluna vulgaris (L.) Hull >Vaccinium vitis-idaea L. > Lycopodium clavatum L. > Orthilia secunda (L.) >Luzula pilosa (L.) Willd. Moss cover is characterized by higher values of specific radionuclide activity as compared with lichen cover, where the epiphytic lichen species have lower 137Cs content than epigeic ones. Soil cover retains the major share of the total radionuclide activity in pine bio-geocenosis and amounts to 76.66 %, while forest litter retains 14.24% and soil mineral layers – 62.42 %. Other components amount to 23.34 %, where pine stands and moss cover account for 12.02 % and 11.04 % respectively, and undergrowth, lichen and grass-shrub cover account only for 0.28 %. The main phytocenosis phytomass falls upon tree stands and accounts for 85.10 %, and moss cover – 14.48 %, while the role of other vegetation layers in this ecotope was insignificant and amounted to 0.42 %. 137Cs total activity distribution by components differs significantly from the distribution of phytomass per area unit. Thus, the maximum share of gross 137Cs total activity is retained by the tree stands (51.49 %) and moss cover (47.32 %). The fraction of the remaining layers is insignificant – 1.19 %, and is presented in the following order by the reduction of radionuclides retention capacity: grass-shrub cover > lichen cover > undergrowth. In pine bio-geocenosis, the key components in the capacity to retain and intensity of radionu-clides biogeochemical circulation are forest soil, tree stands and moss cover.